A Bibliometric Review of Basketball Game: Publication Trends Over the Past Five Decades - Davi Sofyan; Khairul Hafezad Abdullah; Novri Gazali (ASM Science Journal, 2022)
This study aims to examine the evolution of basketball-related scientific publications in the Scopus database by using a variety of bibliometric indicators, such as publication trends, the most influential countries, the most productive authors, and author keywords. From 1969 until 2021, the Scopus database registered 584 basketball publications. This review scrutinised the bibliographic results using Microsoft Excel, Publish or Perish (PoP), and VOSviewer. The production pattern fluctuated throughout the year, but after 2011 it climbed dramatically. In 2006, publications on basketball research had increased to double digits, with 11 documents. Significantly, between 2020 and 2021, 140 publications were published, with 66 in 2020 and 74 in 2021 indicating scholarly interest. The United States is the most productive country, with 210 academic works. J. Sampaio and J. Yanci were the most prolific authors. The Universidad de Granada rose to the top of the productivity rankings. This study has several limitations; the method applied in this study needs to clarify how to find, categorise, and use a database. It’s worth noting that data can also be obtained from other databases.